Implementasi Sistem Informasi Manajemen Gudang (Warehouse Management System) pada PT. Singa Mas Indonesia - Sutanto, Sutanto; Wahidudin, Wahidudin (Politeknik Harapan Bersama, 2023)
So far the process of storing the goods in the warehouse has not been properly installed so that data errors often occur, and it is very impeding a job. The problem of workers or employees in the company is difficult if at any time if there is a data fault, not only that the supply of goods in the warehouse such as stock and placement of goods has not been well-monitoring and detent. OBecause the author raises this problem in order to be able to solve the problem in order to form an effective and efficient system then the best solution is to be made a system of information technology that is able to solve the problem, the system that will be designed later is a warehousing information system capable of monitoring stock of goods, the placement of an item, as well as the availability of information about the features of goods inserted into the warehouse, the programming language that will be used to create its system is Page Hypertext preprocessor (PHP) and MySQL as its databaseandsystem development using waterfallmethod.